Causal Relationship Between Gut Microbiota, Blood Metabolites, and Intervertebral Disc Degeneration: A Two‐Step, Two‐Sample Bidirectional Mendelian Randomization Study - Yi‐Ping Zheng; Dong‐Lin Yang; Lu‐Yang Wang; Xi‐Zhong Zhu; Xing‐Chen Li; Jin‐Hong Miao; Yu‐Sheng Xu (JOR Spine)
ABSTRACT Background Some studies have shown that gut microbiota may be associated with intervertebral disc degeneration. However, the causal effects between gut microbiota and IVDD and whether blood metabolites act as a mediator remain unclear. The objective of this study was to investigate the causal relationship between gut microbiota and intervertebral disc herniation, with a focus on the potential mediating role of blood metabolites. Methods Gut microbiota, blood metabolites, and IVDD data were identified from large‐scale genome‐wide association studies (GWAS) summary data. Then we used Mendelian randomization analysis to investigate the causal relationships between gut microbiota, blood metabolites, and intervertebral disc degeneration, using the inverse variance‐weighted method as the primary outcome measure. Subsequently, we conducted sensitivity analyses to ascertain the robustness of the results by testing for heterogeneity and horizontal pleiotropy. In addition, we explored blood metabolites as a mediating factor in the pathway from gut microbiota to IVDD. Results We identified 6 taxa that were strongly associated with the incidence of intervertebral disc herniation. There were 8 positive and 13 negative causal effects between genetic liability in the blood metabolites and IVDD. The mediation analysis revealed that the connections among genus Comamonas B, family Halomonadaceae, family UBA6960, and IVDD were mediated by ADP to glycine ratio, 1,3‐dimethylurate levels, 3‐hydroxy‐2‐methylpyridine sulfate levels, and Histidine levels. Each of these accounted for 7.77%, 9.04%, 12.56%, and 11.76%, respectively. Conclusions Our study provides evidence supporting a potential causal relationship between certain microbial taxa and intervertebral disc degeneration. This study focuses on the mediation of specific blood metabolites, which suggests that they may represent potential targets for intervention.